2019
DOI: 10.1101/679464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activity-dependent nucleation of dynamic microtubules at presynaptic boutons is required for neurotransmission

Abstract: Highlights:• Excitatory boutons are hotspots for neuronal activity-induced γ-tubulin dependent MT nucleation• The augmin complex is required for the correct polarity of presynaptic de novo nucleated MTs • Presynaptic MT nucleation promotes SV motility and exocytosis at sites of release In Brief: Our results demonstrate that excitatory en passant boutons are hotspots for neuronal activity-induced γ-tubulin-and augmin-dependent oriented MT nucleation, and that the resulting presynaptic de novo nucleated MTs prom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…On the other hand, we observed a high level of the two proteins colocalization in cortical areas that are notably rich in modulatory cholinergic, dopaminergic and serotoninergic en passant varicosities [60][61][62]. Lastly, studies regarding the modulatory role and localization of α-synuclein in brain synapses were mainly focused on excitatory glutamatergic synaptic contacts [8,9,16,63], where they could interact to orchestrate a fine tuning of glutamate release by specialized hotspots, as recently stated by Qu et al [47] in hippocampal cell cultures. As a whole, these studies lay the foundation for further analyses designed to better understand the role of the α-synuclein/α-tubulin interplay in synaptic terminals that possess different neurochemical properties, where they could interact to orchestrate the fine tuning of neurotransmitter release.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…On the other hand, we observed a high level of the two proteins colocalization in cortical areas that are notably rich in modulatory cholinergic, dopaminergic and serotoninergic en passant varicosities [60][61][62]. Lastly, studies regarding the modulatory role and localization of α-synuclein in brain synapses were mainly focused on excitatory glutamatergic synaptic contacts [8,9,16,63], where they could interact to orchestrate a fine tuning of glutamate release by specialized hotspots, as recently stated by Qu et al [47] in hippocampal cell cultures. As a whole, these studies lay the foundation for further analyses designed to better understand the role of the α-synuclein/α-tubulin interplay in synaptic terminals that possess different neurochemical properties, where they could interact to orchestrate the fine tuning of neurotransmitter release.…”
Section: Discussionsupporting
confidence: 59%
“…More interestingly, recent studies in mammalian neurons demonstrated the role of microtubules in the release of synaptic vesicles [58]. Microtubule dynamics is crucial in excitatory en passant varicosities where they are able to correctly target synaptic vesicles to active zones, thus controlling neurotransmission [47]. In this scenario, the results we obtained through multiple approaches, from PLA and confocal spinning disk microscopy to double immunogold pre-embedding and electron microscopy, supply a novel insight into presynaptic functions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Research over the past two decades has revealed that dynamic MTs, in particular, critically contribute to synaptic structure and function within both pre-and postsynaptic compartments 1, 2 . Dynamic MTs regulate synaptic vesicle cycling by providing paths for bidirectional transport between presynaptic terminals, a rate-limiting step in exocytosis at sites of release [3][4][5][6] . In dendritic spines, while the core cytoskeletal structure consists of actin filaments, dynamic MTs originating in the dendritic shaft sporadically enter the spine head and directly impinge on the regulation of spine composition and morphology 7,8 .…”
Section: Introductionmentioning
confidence: 99%